2018
DOI: 10.1080/03639045.2018.1430821
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of electrospray deposition for rapid screening of the cocrystal formation and single step, continuous production of pharmaceutical nanococrystals

Abstract: ESD successfully was utilized to produce pure cocrystals of poorly soluble drugs with different morphologies and sizes ranging from nano to micrometer sizes in one step. This study highlighted the usefulness of ESD for simultaneous preparation and particle engineering of pharmaceutical cocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…We utilized a single-nozzle electrospray system which has been described in detail elsewhere. 15 Briefly, a metal collector was placed 10 cm below the spraying needle and a 20 kV voltage was applied between them. MDF and ERS were dissolved in a 1:1 mixture of methanol and acetone with drug to polymer ratios of 1:5 and 1:10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized a single-nozzle electrospray system which has been described in detail elsewhere. 15 Briefly, a metal collector was placed 10 cm below the spraying needle and a 20 kV voltage was applied between them. MDF and ERS were dissolved in a 1:1 mixture of methanol and acetone with drug to polymer ratios of 1:5 and 1:10.…”
Section: Methodsmentioning
confidence: 99%
“…13 Furthermore, this method can directly produce surfactant-free and solid nanoparticles and does not need further separation and drying steps. The technique has been utilized to produce the nanocrystals, 14 nanococrystals, 15 and drug encapsulated polymeric nanoparticles. 16-19…”
Section: Introductionmentioning
confidence: 99%
“…By considering that carbamazepine, indomethacin, and furosemide have dissolution limited bioavailability, the improved dissolution rates of NCCs may result in higher bioavailability. Emami et al 117 have reported the formation of NCCs of indomethacin-saccharin by using electrospray deposition technique. NCCs with a mean size of 219 nm displayed a 3-fold higher dissolution rate than the cocrystals prepared by the solvent evaporation method.…”
Section: Using Nanosized Cocrystals For Bioavailability Improvementmentioning
confidence: 99%
“…29 After that, a few more studies followed this line of investigation, aiming for pharmaceutical nanococrystal synthesis using bottom-up methods. [30][31][32][33] Simultaneously, top-down methods were also used for pharmaceutical nanococrystal synthesis. For instance, studies regarding wet milling [34][35][36] and high-pressure homogenization 37 can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%